Pomenljive zgodbe, zapisane v osebnih predmetih - Žagar, Janja (Etnolog. Nova vrsta (Ljubljana), 2017)
The article's first part explores selected theoretical ideas, which observe material culture as a constitutive part of man's life, and as the essential juncture of the personal and common. It points out the importance of personified useful objects (clothes), which may become memory objects of biographical value. The second part is based on oral, object and pictorial sources, acquired through sustained research into people's personal appearance and the related materializations of choices, adventures and experiences, memories and discoveries. Stories about objects, which participated in shaping past everyday practices and the special nature of turning points in people's life, are actually fragmentary stories about the lives of people telling their stories, and their affiliations with other people. The article's aim is to draw attention to the exceptional importance of a broad contextualization of the world of objects, which researchers (and museum workers) observe, document, collect, and interpret, even when our attention is directed towards more abstract issues and wider socio-cultural phenomena. The article's first part explores selected theoretical ideas, which observe material culture as a constitutive part of man's life, and as the essential juncture of the personal and common. It points out the importance of personified useful objects (clothes), which may become memory objects of biographical value. The second part is based on oral, object and pictorial sources, acquired through sustained research into people's personal appearance and the related materializations of choices, adventures and experiences, memories and discoveries. Stories about objects, which participated in shaping past everyday practices and the special nature of turning points in people's life, are actually fragmentary stories about the lives of people telling their stories, and their affiliations with other people. The article's aim is to draw attention to the exceptional importance of a broad contextualization of the world of objects, which researchers (and museum workers) observe, document, collect, and interpret, even when our attention is directed towards more abstract issues and wider socio-cultural phenomena.
Keywords: materialna kultura; oblačilna kultura; spominski predmeti; osebna identiteta; muzejske zbirke